Measuring Quality in Automobile Aftersales: AutoSERVQUAL Scale - Yasin Galip Gencer; Ulas Akkucuk (Amfiteatru Economic)
It is becoming more important to accurately measure the level of quality in services and especially automobile related services such as after sales service. This study aims to generate a survey to measure the service quality in automobile aftersales services, eventually to be called AutoSERVQUAL. The roadmap for this survey generation process starts by examining the service quality measurement scales in literature first and then continues by the adaptation process of SERVQUAL over automobile aftersales customers. Each and every step in survey generation processes is explained starting from expert interviews and finally statistical analyses. Starting with 45 candidate questions, the study offers a 28 item scale that can measure service quality in after sales car services with high reliability. The scale can be extended to cover aftersales services in general for any type of product and also could be used as input to other models such as QFD and MADM. The scale should also be empirically tested in other countries with specific requirements for after sales services.